2020
DOI: 10.1037/xge0000674
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and social bonding: Effect of naltrexone on feelings of social connection and ventral striatum activity to close others.

Abstract: Close social bonds are critical to immediate and long-term well-being. However, the neurochemical mechanisms by which we remain connected to our closest loved ones are not well understood. Opioids have long been theorized to contribute to social bonding via their actions on the brain. But feelings of social connection toward one’s own close others and direct comparisons of ventral striatum (VS) activity in response to close others and strangers, a neural correlate of social bonding, have not been explored. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…Increased negative facial reactions after opioid blockade were also reported during viewing of smiling faces [84], consistent with a role for MOR signalling in automatic behavioural responses (mimicry) that support social bonding [66]. Moreover, opioid antagonism has been reported to reduce ratings of the feeling of being connected to other people [56,57]. The magnitude of the shift in feelings of connectedness is modest, comparable to effect sizes of acute opioid drug effects on other high-value rewards.…”
Section: Acute Opioid Effects In Human Researchmentioning
confidence: 63%
“…Increased negative facial reactions after opioid blockade were also reported during viewing of smiling faces [84], consistent with a role for MOR signalling in automatic behavioural responses (mimicry) that support social bonding [66]. Moreover, opioid antagonism has been reported to reduce ratings of the feeling of being connected to other people [56,57]. The magnitude of the shift in feelings of connectedness is modest, comparable to effect sizes of acute opioid drug effects on other high-value rewards.…”
Section: Acute Opioid Effects In Human Researchmentioning
confidence: 63%
“…Increased negative facial reactions after opioid blockade were also reported during viewing of smiling faces (Meier et al, 2016), consistent with a role for MOR signalling in automatic behavioural responses (mimicry) that support social bonding (Lakin et al, 2003). Moreover, opioid antagonism has been reported to reduce ratings of the feeling of being connected to other people (Inagaki et al, 2016;Inagaki et al, 2020). The magnitude of the shift in feelings of connectedness is modest, comparable to effect sizes of acute opioid drug effects on other high-value rewards.…”
Section: Acute Opioid Effects In Human Researchmentioning
confidence: 96%
“…First, assuming that having and maintaining social connections is vital to human functioning, the opioid theory of social attachment suggests that endogenous opioids are released during these experiences of social bonding, which then underlie the pleasant feelings of social bonding to positively reinforce the formation of such bonds. Based on this theory, studies have shown that naltrexone reduces feelings of social connection, especially to one’s closest others [ 21 , 22 ]. Reduced positive associations with significant others, especially the deceased, may make bereavement feel less lonely and isolated while diminishing the reward derived from reminiscing about the deceased.…”
Section: Introductionmentioning
confidence: 99%